Anisotropy in the magnetic interaction and lattice-orbital coupling of single crystal Ni3TeO6. Issue 1 (December 2018) - Ghosh, Anirudha; Chen, K.-H.; Qiu, X.-S.; Hsieh, S.; Shao, Y.; Du, C.; Wang, H.; Chin, Y.; Chiou, J.; Ray, Sekhar; Tsai, H.; Pao, C.; et al.
Abstract This investigation reports on anisotropy in the magnetic interaction, lattice-orbital coupling and degree of phonon softening in single crystal Ni3 TeO6 (NTO) using temperature- and polarization-dependent X-ray absorption spectroscopic techniques. The magnetic field-cooled and zero-field-cooled measurements and temperature-dependent NiL 3, 2 -edge X-ray magnetic circular dichroism spectra of NTO reveal a weak Ni-Ni ferromagnetic interaction close to 60 K (T SO : temperature of the onset of spin ordering) with a net alignment of Ni spins (the uncompensated components of the Ni moments) along the crystallographicc -axis, which is absent from theab -plane. Below the Néel temperature, T N 52 K, NTO is stable in the antiferromagnetic state with its spin axis parallel to thec -axis. The NiL 3, 2 -edge X-ray linear dichroism results indicate that aboveT SO, the Ni 3d e g electrons preferentially occupy the out-of-plane 3d 3z 2 −r 2 orbitals and switch to the in-plane 3d x 2 −y 2 orbitals belowT SO . The inherent distortion of the NiO6 octahedra and anisotropic nearest-neighbor Ni-O bond lengths between thec -axis and theab -plane of NTO, followed by anomalous Debye-Waller factors and orbital-lattice in conjunction with spin-phonon couplings, stabilize the occupied out-of-plane (3d 3z 2 −r 2 ) and in-plane (3d x 2 −y 2 ) Nie g orbitals above and belowT SO, respectively.